2008
DOI: 10.1128/aac.00414-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Linezolid against Clinical Isolates of Mycobacterium tuberculosis Complex Isolated in Taiwan over 10 Years

Abstract: Significant increases in the MICTuberculosis (TB) is one of the major causes of death worldwide. The global prevalence of mycobacterial infection has been estimated to be 32% (1.9 billion people), with 8 million new cases of TB diagnosed annually and an average case fatality rate of 23% (11). In the year 2003, the incidence and mortality rate of TB in Taiwan were reported at 62.38 and 5.80 per 100,000 people, respectively (2), and TB is considered a more serious public health problem in southern than in northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 9 publications
2
23
0
1
Order By: Relevance
“…The MICs for linezolid ranged from 0.125 to 0.5 mg/mL for all tested isolates. The MIC against M. tuberculosis H37Rv was 0.5 mg/mL, in accordance with previously published data (11). There were no differences in linezolid MIC 50 (MICs for 50z of the organisms) and MIC 90 values among susceptible, INH-resistant, MDR, and XDR groups.…”
supporting
confidence: 77%
“…The MICs for linezolid ranged from 0.125 to 0.5 mg/mL for all tested isolates. The MIC against M. tuberculosis H37Rv was 0.5 mg/mL, in accordance with previously published data (11). There were no differences in linezolid MIC 50 (MICs for 50z of the organisms) and MIC 90 values among susceptible, INH-resistant, MDR, and XDR groups.…”
supporting
confidence: 77%
“…Previous studies have shown that linezolid has good in vitro activity against both drug-susceptible and MDR strains of M. tuberculosis, with MIC values of 1 mg/L or lower (2,30). The clinical use of linezolid in the treatment of TB, however, is limited to five studies of patients with MDR-TB (13)(14)(15)(16)31).…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies evaluated the efficacy, safety and tolerability of the linezolid containing regimes for treating MDRand XDR-TB cases. However, most were restricted mainly to case reports, a retrospective analysis and small case series [14][15][16][17][18][19][28][29][30][31]. This is a prospective, multicentre, randomised study on efficacy, safety and tolerability of linezolid for treating XDR-TB.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in vitro have shown good activity of linezolid against various species of mycobacteria, including drug-resistant mycobacterial strains [12][13][14]. Recent case studies and retrospective analysis have suggested that linezolid may be effective in treating MDR-TB and XDR-TB [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%